A critical analysis of auditors' perception of the impact of Section 404 of the Sarbanes Oxley Act on audit quality: an Egyptian perspective. (2010) - Hegazy, Mohamed; Kamer, Noha Abou
The recent accounting scandals that have occurred in the USA have resulted in the issuance of the Sarbanes Oxley Act (SOX), with emphasis on Section 404 related to enhancing the companies' internal controls. This research study critically examines Section 404 requirements, surveying a sample of Egyptian auditors in a number of audit firms with international affiliations about their perception of the expected costs and benefits that could result from applying Section 404, and whether such requirements could have a positive impact on the quality of audit. The results provide evidence based on auditors' opinions that the benefits associated with Section 404 applications are expected to outweigh its costs, with possible reduction of Section 404 costs in the future period. Moreover, the results indicate that both the additional audit procedures required in the audit of internal control over financial reporting (ICOFR) and the increased legal liability that will be imposed on auditors through compliance with Section 404 requirements are expected to improve the quality of the audit process. The results of the study call for the application of similar requirements of Section 404 taking into consideration the characteristics and other elements affecting the Egyptian businesses, accounting and auditing profession.